2012
DOI: 10.3109/1354750x.2012.715672
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione levels in human tumors

Abstract: This review summarizes clinical studies in which glutathione was measured in tumor tissue from patients with brain, breast, gastrointestinal, gynecological, head and neck and lung cancer. Glutathione tends to be elevated in breast, ovarian, head and neck and lung cancer and lower in brain and liver tumors compared to disease-free tissue. Cervical, colorectal, gastric and esophageal cancers show both higher and lower levels of tumor glutathione. Some studies show an inverse relationship between patient survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
381
1
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(414 citation statements)
references
References 114 publications
(259 reference statements)
19
381
1
13
Order By: Relevance
“…Glutathione (GSH) is an important intracellular antioxidant that prevent cellular component damage caused by reactive oxygen species. It has been suggested that GSH tends to be elevated in breast, ovarian, head/neck, and/or lung cancers as compared to disease‐free tissues 59. In tumor cells, high GSH level can trigger disulfide bond (—S—S—) cleavage.…”
Section: Bihlas For Controlled Releasementioning
confidence: 99%
“…Glutathione (GSH) is an important intracellular antioxidant that prevent cellular component damage caused by reactive oxygen species. It has been suggested that GSH tends to be elevated in breast, ovarian, head/neck, and/or lung cancers as compared to disease‐free tissues 59. In tumor cells, high GSH level can trigger disulfide bond (—S—S—) cleavage.…”
Section: Bihlas For Controlled Releasementioning
confidence: 99%
“…В частности, в различных типах опухолей наблюдается повышенный уровень GSH, который является важным внутриклеточным антиоксидантным фактором, снижающим уровень АФК и участвующим в регуляции различных тиол-зависимых и АФК-зависимых сигнальных путей [4,8,9,18].…”
Section: результаты и обсуждениеunclassified
“…Данные литературы [9] свидетельствуют о том, что единой направленности изменений содержания GSH в опухолях различной гистологической структуры и различной локализации нет. При раке яичников, раке молочной железы, опухолях орофарингеальной зоны был обнаружен, как правило, более высокий уровень GSH в опухолевой ткани.…”
Section: результаты и обсуждениеunclassified
See 2 more Smart Citations